Internasional Talkshow bersama mahasiswa Nigeria dan Sudan pada siswa MBS Muhammadiyah Kedung Kandang Kota Malang - Bahrul Ulum; Wildani Rosyada (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
The medium of international communication is English. The language used in general to communicate between countries, therefore English can be said to be universal, where its use is not only as a communication bridge in everyday life but also for international communication. At the education level, English is taught to 11th grade high school students to provide them with international communication skills. However, the problem that arises is that grade 11 students feel they are still lacking in mastering English to communicate. Therefore, this article aims to report on PKM activities in providing motivation and training in talkshow concepts to 35 students of grade 11 MBS Muhammadiyah boarding school Kedung Kandang Malang City so that students are motivated and motivated in honing their English mastery, having good insight. international in nature and useful as a tool to answer the challenges of the development of science in the era of globalization. The activity method used is the presentation method. Meanwhile, to collect data, the author uses a review of service activities. After conducting this “international Talkshow” activity, 11th grade students have the provision of international communication. As a follow-up, it is necessary to do more to develop and train English continuously for 11th grade students of SBM Malang.